Challenges of African Growth : Opportunities, Constraints, and Strategic Directions - Ndulu, Benno J. (Washington, DC: World Bank, 2012)
Poverty in Africa is largely the outcome of slow growth. With the region hosting 10 percent of the world's population but a staggering 30 percent of the world's poor, the challenges it faces are enormous but not insurmountable. The message of this book is clear - poverty-eradicating development in Africa is possible. In fact, there are indications that Africa is at a turning point, and there is growing momentum among front-runner economies in the region toward higher and sustained growth. This study challenges African countries and their development partners to consolidate and continue this momentum and to exploit the advantages of the continent as a latecomer, particularly in innovation and in drawing lessons from successful export-led growth experiences in Asia and Latin America.